1985
DOI: 10.1007/bf00157827
|View full text |Cite
|
Sign up to set email alerts
|

Ten years experience with choroidal angiography using indocyanine green dye: a new routine examination or an epilogue?

Abstract: The choroidal circulation can be studied by an angiographic technique which utilizes near-infrared light wavelengths and a biocompatible dye, indocyanine green (CardiogreenR). Near-infrared light is less absorbed than visible light by the pigment epithelium and the macular xanthophyll, and indocyanine green (ICG) dye doesn't leak from the choriocapillaris as sodium fluorescein dye typically does. Due to the high rate of choroidal blood flow, a fundus camera adapted with special filters and a continuous light s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(76 citation statements)
references
References 64 publications
2
74
0
Order By: Relevance
“…Because this angiographic finding is typical of retinal macroaneurysms (Schneider et al 1997), we diagnosed this mass lesion as a large retinal macroaneurysm. ICG angiography, with its absorption and emission peak in the near-infrared spectrum, allows observation of the lesion through hemorrhage (Flower & Hochheimer 1973;Hayashi & DeLaey 1985;Bischoff & Flower 1985). This ability is not possible with fluorescein angiography, which uses blue or green light in the shorter wavelengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because this angiographic finding is typical of retinal macroaneurysms (Schneider et al 1997), we diagnosed this mass lesion as a large retinal macroaneurysm. ICG angiography, with its absorption and emission peak in the near-infrared spectrum, allows observation of the lesion through hemorrhage (Flower & Hochheimer 1973;Hayashi & DeLaey 1985;Bischoff & Flower 1985). This ability is not possible with fluorescein angiography, which uses blue or green light in the shorter wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…The ICG angiographic sequence also was observed continuously on a videoscreen, which showed a pulsation of the macroaneurysm. In addition, because ICG is highly protein-bound (Flower & Hochheimer 1973;Hayashi & DeLaey 1985;Bischoff & Flower 1985), the dye leaks very slowly into the lumen of the macroaneurysm. This feature enables a detailed examination of the anatomical relationship between the retinal artery and the lumen of the macroaneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…129 These results would support the concept that CEC and REC behave differently under hyperglycaemia, and may explain, at least in part, some of the clinical differences observed in the frequencies/prevalences of DR and choroidopathy. [6][7][8][9] Western blotting indicated that claudin-5 protein expression was also higher in RECs, whereas JAM-A and C and VE-Cadherin levels were similar. 110 High-glucose conditions (equivalent to hyperglycaemia) significantly increased the permeability in both REC and CEC monolayers, although the increase was higher for RECs.…”
Section: Scientific Basismentioning
confidence: 99%
“…4,5 Diabetic choroidopathy is a less well-studied entity, and is thought to occur in the advanced stages of diabetic eye disease. [6][7][8][9] As such, the retinal and choroidal vascular beds seem to be affected differently by diabetes. Diabetes and hyperglycaemia have obvious effects on intraocular vascular endothelial cell (EC) permeability, adhesion to leukocytes, as well as angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation